SPECIFIC OBJECTIVES OF THE STUDY RELATED TO THE USE OF DIGITAL TECHNOLOGIES IN TEACHING ECONOMICS VOCABULARY TO B2 LEVEL LEARNERS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
Annotation: This article explores the specific objectives of studying the use of digital technologies in enhancing the lexical competence of economics students at the B2 level. The primary goal is to investigate how digital tools can support vocabulary acquisition, retention, and contextual understanding of economics-specific terminology. The study examines the role of interactive simulations, digital flashcards, collaborative learning platforms, and personalized learning technologies in helping students master economics vocabulary. By focusing on practical applications, this research aims to identify effective strategies for integrating digital technologies into economics education to improve students’ ability to use specialized terms confidently in both academic and professional settings. The findings are intended to contribute to the development of more effective pedagogical approaches for teaching economics vocabulary.